Ethical dimensions in the health professions - Doherty, Regina F.; Purtilo, Ruth B. (St. Louis, Missouri : Elsevier, 2021)
Build the skills you need to understand and resolve ethical problems! Ethical Dimensions in the Health Professions, 7th Edition provides a solid foundation in ethical theory and concepts, applying these principles to the ethical issues surrounding health care today. It uses a unique, six-step decision-making process as a framework for thinking critically and thoughtfully, with case studies of patients to illustrate ethical topics such as conflict of interest, patient confidentiality, and upholding best practices. Written by Regina F. Doherty, an educator and occupational therapist, this book will help you make caring and effective ethical choices that improve patient care and outcomes -- Provided by the publisher
Previous edition: 2016
Includes bibliographical references and index
Keywords: Medical ethics; Ethics, Professional; Patient Rights -- ethics